Utilizing the Film The Founder to Improve Students’ English Listening Skills - Nur Indah Pratiwi; Abdul Wahid; Lely Novia (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2025)
This study explores the effectiveness of using the film The Founder as a medium to enhance the English listening skills of students in the Business English Communication (BEC) Study Program, Class of 2023. A pre-experimental, one-group pretest-posttest design was employed with a sample of 65 students. Data were collected through listening comprehension tests administered before and after the film-based intervention and analyzed using SPSS 22. The pre-test yielded an average score of 37.31 (range: 5.00–85.00), while the post-test average significantly increased to 75.57 (range: 30.00–100.00). A paired sample t-test indicated a statistically significant difference between the pre- and post-test scores (p < 0.001). These findings suggest that films, particularly The Founder, serve as engaging and effective tools for improving students’ English listening comprehension. Furthermore, the relatively low standard deviation compared to the mean indicates consistent improvement across participants, reinforcing the pedagogical value of audiovisual media in EFL instruction.